âWhat Makes You Different?â: the Process of Teacher Cognitive Development in Pre-service EFL Teacher Education - Misrohmawati, Elys R.R. (Sebelas Maret University, 2016)
English as a foreign language (EFL) teachersâ practice in the classroom depends on teacher cognition. It is what teachers think, know, and believe about EFL teaching. To be a good teacher, they should have cognition that contributes to the success of teaching. Pre-service teacher education must be designed to support cognitive development that has potentials to create effective English classroom teaching and learning activities in the future professional practice. The role of teacher education is not only in cognitive development, but also in constructing new positive cognition if the students of EFL teacher education have prior negative English learning experience. This paper discusses cognitive development in three area, i.e. material design, teaching methodology, and learning context. Hopefully, this study has positive impact for the conduct of teaching practice on pre-service EFL teacher education courses.